The Influence of Student-Centered Learning Implementation on Fostering Student Independence at Wittaya Panya School Thailand - Lathifah, Zahra Khusnul; Putri, Eka Apriani; Efendi, Irwan; Rusli, Radif Khotamir; Radiamoda, Anwar M.; Meatam, Adul (International Journal of Multidisciplinary Research of Higher Education, 2025)
A child's independence can flourish and develop further when intentional efforts are made to nurture this trait. In many cases, students tend to rely heavily on their teachers for assistance during classroom activities. Efforts to cultivate character aligned with the cultural values of Thailand nation extend beyond the confines of the school setting; they permeate children's daily lives through consistent introduction and habituation practices. Character development is encouraged not only through classroom and extracurricular activities but also through intentional integration into their everyday interactions and routines. This study thus seeks to explore the impact of the Student-Centered Learning (SCL) approach on fostering student independence at Wittaya Panya School, Thailand. Utilizing a qualitative, descriptive research methodology, this study was conducted at Wittaya Panya School in Khlong Chalem, Kong Ra District, Patthalung Province, Thailand. Data sources comprised primary and secondary data, collected through observation, interviews, and literature review. Findings from this study indicate that by employing a Student-Centered Learning approach, teachers can effectively instill and strengthen the independence of students, which can be integrated into their daily learning processes.